Equitable Policy Reform through an Interest-Balancing Approach as a Solution for the Development of Solar and Wind Energy in Indonesia - Fareh Prameswari; Putra Chinto Chamicho; Gregorius Eka Januario CAB (Jurnal Mengkaji Indonesia, 2025)
Abstract: The dominance of fossil fuels in Indonesia's energy sector has led to environmental degradation and growing energy subsidies. Amid escalating global demands for sustainable energy, Indonesia possesses vast potential in solar and wind resources, yet remains underutilized due to high capital costs, policy inconsistencies, and regulatory uncertainties. Purpose: This study aims to explore how equitable policy reform, through an interest-balancing approach, can facilitate the acceleration of solar and wind energy development in Indonesia. Design/Methodology/Approach: Employing normative legal research with statute and conceptual approaches, the study critically analyzes legal frameworks, government regulations, and doctrinal views on renewable energy investment. Findings: The findings reveal that the Risk-Based Online Single Submission (OSS RBA) system, while intended to streamline licensing, often exacerbates environmental risks and excludes community participation. Moreover, sudden regulatory shifts, lack of legal enforcement, and weak post-licensing supervision undermine investor confidence. Drawing from international practices such as New Zealand’s Treaty of Waitangi-based model and Canada’s implementation of Free, Prior, and Informed Consent (FPIC), the paper argues for a balanced policy model integrating investor certainty, environmental protection, and community rights. Originality/value: This article contributes original insights into the shortcomings of Indonesia’s current regulatory ecosystem and proposes the adoption of an interest-balancing approach informed by the Economic Analysis of Law and the Triple Bottom Line framework (Profit, People, Planet). It provides a novel prescriptive legal solution for enabling a more inclusive, sustainable, and investment-friendly environment for renewable energy development.